The Relationship between Autism Spectrum Disorder and Melatonin during Fetal Development - Yunho Jin (Molecules, 2018)
The aim of this review is to clarify the interrelationship between melatonin and autism spectrum disorder (ASD) during fetal development. ASD refers to a diverse range of neurodevelopmental disorders characterized by social deficits, impaired communication, and stereotyped or repetitive behaviors. Melatonin, which is secreted by the pineal gland, has well-established neuroprotective and circadian entraining effects. During pregnancy, the hormone crosses the placenta into the fetal circulation and transmits photoperiodic information to the fetus allowing the establishment of normal sleep patterns and circadian rhythms that are essential for normal neurodevelopment. Melatonin synthesis is frequently impaired in patients with ASD. The hormone reduces oxidative stress, which is harmful to the central nervous system. Therefore, the neuroprotective and circadian entraining roles of melatonin may reduce the risk of neurodevelopmental disorders such as ASD.